Serum Uromodulin as early marker for ischemic acute kidney injury and nephron loss: association with kidney tissue distribution pattern - Vonbrunn, Eva; Ebert, Nadja; Cordasic, Nada; Amann, Kerstin Ute; Büttner, Anke; Büttner-Herold, Maike; Scherberich, Jürgen E.; Daniel, Christoph (Journal of Translational Medicine, 2025)
Background: Uromodulin (UMOD) is expressed in kidneys and is mainly excreted in the urine, although a smaller amount is also released into the serum. Here, we investigated UMOD in acute kidney injury (AKI), with particular focus on the utility of serum UMOD as marker for nephron loss. Methods: Blood and kidney samples were collected 6 h, 24 h, 3 days and 8 weeks after ischemia/reperfusion (I/R) in a rat model. To investigate the impact of nephron number on UMOD levels, sera and tissue from healthy, uninephrectomized (Unx) and 5/6-nephrectomized (Snx) rats were analyzed. Histological changes, kidney function and cell damage were evaluated and serum UMOD, Umod mRNA expression and distribution of UMOD protein in the kidney were examined. Results: In AKI, kidney function was markedly impaired 24 h after I/R, while kidney injury and serum UMOD was increased transiently. Simultaneously, the amount of UMOD-positive kidney cells rapidly decreased 24 h after I/R compared to healthy kidneys, and mRNA expression of Umod was lowest on days 1–3 after I/R. Serum UMOD correlated with nephron number showing the highest levels in healthy rats, which were reduced after Unx and further reduced after Snx. Conclusion: In an AKI model with severe tubular damage, a transient increase in UMOD serum levels in parallel with loss of UMOD-positive cells suggests temporary release of UMOD from destroyed tubular cells into the blood. Serum UMOD appears to be not only a marker of chronic renal failure but also of acute loss of functional and cellular integrity of kidney epithelia in AKI.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Acute kidney injury; Ischemia/reperfusion; Nephron loss; Tamm-Horsfall protein; Uromodulin